2021
DOI: 10.1371/journal.pone.0256168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma PAF acetylhydrolase activity measurements as a biomarker of anaphylaxis: Cross-sectional study

Abstract: Introduction Platelet-activating factor (PAF) has a direct role as a mediator in the pathogenesis of various disorders with an inflammatory component, including those with allergic aetiology. The peripheral blood concentration of PAF is dynamically regulated by plasma PAF acetylhydrolase (PAF-AH). Previous research suggest that low activity of plasma PAF-AH could be a predictive marker for increased severity of some types of allergic hypersensitivity reactions–especially anaphylaxis. The purpose of the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Multiple studies have implicated the critical roles of the potent lipid mediator, Platelet‐activating factor (PAF) in mediating the responses of diverse stimuli in disease pathophysiologies, including cancer and cancer therapies. 22 , 23 , 24 , 25 , 26 , 27 Relevant to cancer therapies, studies, including ours, have demonstrated that therapeutic agents due to their ability to generate free radicals, produce PAF and PAF‐like lipids as a bystander effect. 26 , 27 These PAF lipids via activating a G‐protein coupled, PAF‐receptor (PAFR), expressed on various cell types, modulate their efficacy of therapeutic agents in experimental tumor models, including skin cancer.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Multiple studies have implicated the critical roles of the potent lipid mediator, Platelet‐activating factor (PAF) in mediating the responses of diverse stimuli in disease pathophysiologies, including cancer and cancer therapies. 22 , 23 , 24 , 25 , 26 , 27 Relevant to cancer therapies, studies, including ours, have demonstrated that therapeutic agents due to their ability to generate free radicals, produce PAF and PAF‐like lipids as a bystander effect. 26 , 27 These PAF lipids via activating a G‐protein coupled, PAF‐receptor (PAFR), expressed on various cell types, modulate their efficacy of therapeutic agents in experimental tumor models, including skin cancer.…”
Section: Introductionmentioning
confidence: 81%
“…PAF is a potent phospholipid mediator, which plays critical roles in various inflammatory and pathological conditions, including cancer growth. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 31 , 34 , 35 , 36 , 37 , 38 PAF and other PAF‐like agonists mediate their effects via binding to a seven‐transmembrane G protein‐coupled PAFR, expressed on various cell types, including epidermal keratinocytes. 34 , 35 , 36 Agents possessing pro‐oxidative stressors' ability such as ultraviolet B (UVB), cigarette smoking, and therapeutic agents can generate an exaggerated amount of reactive oxygen species (ROS) and produce increased levels of PAF and PAF‐like oxidized lipids.…”
Section: Discussionmentioning
confidence: 99%
“…PAF-AH is a hydrolase of PAF and inactivates PAF by catalyzing the hydrolysis of acetyl esters at the SN-2 site of PAF [44]. PAF is a pro-inflammatory lipid medium of glycerophosphoric choline expressed in a variety of immune cells, which activates immune cells by binding to receptors and is widely involved in the regulation of various allergic diseases such as asthma and AD [45][46][47]. Therefore, we used ELISA to detect the content of PAF in the skin of the modeled mice.…”
Section: Wfdc12 Affected the Activity Of Epidermal Serine Hydrolasementioning
confidence: 99%
“…A low PAF acetylhydrolase activity is correlated with increased severity of allergic reactions in humans. [39][40][41] J€ onsson et al 39 showed that IgG-dependent anaphylaxis to NMBAs in humans is preferentially triggered via FcgR-mediated neutrophil activation and associated with the production of neutrophil extracellular traps (NETs). In this study, concentrations of anti-NMBA IgG, markers of FcgR activation, PAF release and neutrophil activation correlated with anaphylaxis severity.…”
Section: Non Immunoglobulin E Mediated Endotypesmentioning
confidence: 99%
“…As PAF concentration is extremely difficult to measure, another marker of interest for this endotype is PAF acetylhydrolase activity, as this enzyme regulates PAF levels. A low PAF acetylhydrolase activity is correlated with increased severity of allergic reactions in humans 39–41 …”
Section: Non Immunoglobulin E Mediated Endotypesmentioning
confidence: 99%